Patter - Kearney, Douglas (Book collections on Project MUSE., 2014)
For a couple struggling with infertility, conception is a war against their bodies. Blood and death attend. But when the war is won, and life stares, hungry, in the parents' faces, where does that violence, anxiety, and shame go? The poems in Patter re-imagine miscarriages as minstrel shows, magic tricks, and comic strips; set Darth Vader against Oedipus's dad in competition for Father of the Year; and interrogate the poet's family's stint on reality TV. In this, his third collection, award-winning poet Douglas Kearney doggedly worries the line between love and hate, showing how it bleeds itself into fatherhood.